Past, Present, and the Politics of Witch Hunts - Morris, Kathryn (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2024)
This article compares contemporary political rhetoric from and around Donald Trump with early modern discourse on witchcraft. Trump frequently and explicitly positions himself as the victim of political “witch hunts.” I will argue that he also deploys rhetoric that parallels early modern arguments connecting the persecution of witches with the exercise of sovereign authority, implicitly putting him in the position of the witch hunter. The article focuses on two Renaissance texts, Jean Bodin’sOn the Demon-Mania of Witches (1580) and King James VI and I’s Daemonologie (1597), highlighting the ways in which both the contemporary and early modern discourses appeal to disruptive conspiracies, the threat of political and epistemic chaos, and the targeting of legitimate political authority. The language and logic of witchcraft, past and present, provides Trump and Trumpians with a powerful rhetorical resource.